2012
DOI: 10.1097/gme.0b013e3182443137
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen deficiency accelerates aging of the optic nerve

Abstract: Objective To provide a comprehensive review on hormone-based pathophysiology of aging of the optic nerve and glaucoma. Methods A literature review and expert opinions. Results Glaucoma, a group of intraocular pressure-related optic neuropathies, is characterized by the slow progressive neurodegeneration of retinal ganglion cells and their axons resulting in irreversible visual sensitivity loss and blindness. Increasing evidence suggests that glaucoma represents the accelerated aging of the optic nerve and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 68 publications
2
80
1
Order By: Relevance
“…It is unknown the real contribution of circulating steroids in the retinal local synthesis, if the local E2 production may be regulated by circulating levels like it is suggested for other extragonadal organs including the brain [15,41], thus if local levels are high when plasma levels are low. Changes in circulating levels have been suggested to influence retinal/ocular diseases; oestrogen deficiency has showed to accelerate aging of the optic nerve [147]. The exact E2 physiological role and ERs' molecular mechanisms are still elusive.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…It is unknown the real contribution of circulating steroids in the retinal local synthesis, if the local E2 production may be regulated by circulating levels like it is suggested for other extragonadal organs including the brain [15,41], thus if local levels are high when plasma levels are low. Changes in circulating levels have been suggested to influence retinal/ocular diseases; oestrogen deficiency has showed to accelerate aging of the optic nerve [147]. The exact E2 physiological role and ERs' molecular mechanisms are still elusive.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…16 Furthermore, postmenopausal hormone (PMH) use was associated with a reduced risk of high-tension POAG in the Nurses Health Study. 17 For more details regarding the critical role of estrogen in POAG pathogenesis, see a recent review by Vajarant and Pasquale 18 in Menopause.…”
mentioning
confidence: 98%
“…Another interesting result in this study was the one supporting genetic differences between female and male POAG. Research has shown evidence that estrogen has protective effects against POAG potentially by promoting higher production of collagen fibers that increase flexibility of the eye, thus reducing IOP [164][165][166]. This could explain our findings given that genetic variation in the estrogen pathways may have a higher impact in women than in men.…”
Section: Genetic Correlation Studiessupporting
confidence: 32%
“…POAG heritability) was still unknown. Further, epidemiological studies indicate that higher estrogen levels may help prevent POAG [164][165][166] and that the prevalence of POAG differs between sexes (the prevalence in men is higher than in women). Therefore, using genotype data of Australian cases and controls, we investigate the contribution of common and rare variants to POAG and we assess whether there are differences between POAG sexes (generated by genetic variants acting in men but not women, or vice versa).…”
Section: Primary Open Angle Glaucoma and Age-related Macular Degeneramentioning
confidence: 99%